2010
DOI: 10.1111/j.1399-3046.2009.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, impact, and treatment of portal and hepatic venous complications following pediatric liver transplantation: A single-center 12 year experience

Abstract: PVT or PVS and HVOO are known causes of graft and patient loss after pediatric liver transplantation. Increased incidences of these complications have been reported in partial livers including DDSLT or LDLT. From 1997 to 2008, 241 consecutive pediatric patients received 271 hepatic grafts at a single center. Median follow-up is 1856 days. Surgical technique, demographics, lab values, and radiologic imaging procedures were obtained utilizing OTTR to evaluate the relationship of portal and hepatic complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
5

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 25 publications
(52 reference statements)
3
36
0
5
Order By: Relevance
“…Heffron et al reported a PVC incidence of 2.2% for a cohort of 271 patients (156 full size grafts and 115 partial liver grafts). The BW values for patients receiving whole liver and partial grafts were 34.9 and 16.7 kg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Heffron et al reported a PVC incidence of 2.2% for a cohort of 271 patients (156 full size grafts and 115 partial liver grafts). The BW values for patients receiving whole liver and partial grafts were 34.9 and 16.7 kg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The main causes of graft loss in the first week include primary nonfunction, hepatic artery thrombosis (HAT) or portal vein thrombosis (PVT), systemic sepsis, and multiorgan failure (<10%). Other significant complications are acute rejection (AR; 50%), chronic rejection (CR; 10%), biliary leaks and strictures (5%‐25%), viral infections [especially cytomegalovirus (CMV) and Epstein‐Barr virus (EBV)], acute kidney injury, and fluid imbalance . The 1‐year patient survival rate is 90%, and the survival rate is 75% at 15 to 20 years with good quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…The approach to thrombosis prevention remains largely empirical, and practices vary widely between centers. Hardikar et al [25] prospectively evaluated a standardized perioperative protocol in 40 transplant recipients which incorporated regular AT concentrate to maintain levels > 70%, daily fresh frozen plasma (FFP) 15 mL kg À1 to maintain protein C/S levels, and low-dose unfractionated heparin (UFH) [28] USA P/C LT 0-18 PGE1, ASA HAT 2.7% Heffron (2010) [75] USA P/C LT 0-18 PGE1, ASA PVT < 1% Ikegami (2006) [76] Japan P/C LDLT All LMWH, AT, protease inhibitor, PGE1, FFP HAT 5.4%…”
Section: Thromboprophylaxismentioning
confidence: 99%